2021
DOI: 10.1152/jn.00310.2020
|View full text |Cite
|
Sign up to set email alerts
|

Common and distinct muscle synergies during level and slope locomotion in the cat

Abstract: Although it is well established that the motor control system is modular, the organization of muscle synergies during locomotion and their change with ground slope are not completely understood. For example, typical reciprocal flexor-extensor muscle synergies of level walking in cats break down in downslope: one-joint hip extensors are silent throughout the stride cycle, whereas hindlimb flexors demonstrate an additional stance phase-related EMG burst (Smith et al. 1998a). Here we investigated muscle synergies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

6
2

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 132 publications
2
10
0
Order By: Relevance
“…Several studies have observed the presence of a second burst in the ST muscle and its close synergist BFP (hip extensors/knee flexors) just before paw contact during quadrupedal locomotion ( Chanaud et al, 1991 ; Smith et al, 1993 ; Desrochers et al, 2019 ; Klishko et al, 2021 ). Although not always present at slow speeds ( Smith et al, 1993 ), this burst decelerates forward movement of the limb before paw contact, particularly at faster speeds ( Wisleder et al, 1990 ; Smith et al, 1993 ; Pratt et al, 1996 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have observed the presence of a second burst in the ST muscle and its close synergist BFP (hip extensors/knee flexors) just before paw contact during quadrupedal locomotion ( Chanaud et al, 1991 ; Smith et al, 1993 ; Desrochers et al, 2019 ; Klishko et al, 2021 ). Although not always present at slow speeds ( Smith et al, 1993 ), this burst decelerates forward movement of the limb before paw contact, particularly at faster speeds ( Wisleder et al, 1990 ; Smith et al, 1993 ; Pratt et al, 1996 ).…”
Section: Resultsmentioning
confidence: 99%
“…During level quadrupedal treadmill locomotion, IP and SRT muscles display a single period of activity during the swing phase ( Figure 8A ; Rasmussen et al, 1978 ; Halbertsma, 1983 ; de Leon et al, 1998 ; Desrochers et al, 2019 ). However, during downslope walking, the IP and SRT become active during stance ( Smith et al, 1998 ; Klishko et al, 2021 ) to better control the descent ( Gregor et al, 2006 ). The SRT and IP muscles also display a second burst of activity during the stance phase in the spinal state ( BĂ©langer et al, 1996 ; de Leon et al, 1998 ; Rossignol and Bouyer, 2004 ) and in the Intact2 condition ( Figure 8A ; de Leon et al, 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…The organization of the mammalian CPG controlling rhythmic behaviors, such as different forms of locomotion, scratching, and paw shaking, is not fully understood. Although many researchers agree that some common elements of the CPG network can be used to control different rhythmic movements, there is an ongoing debate about whether the spinal CPG has a single-level or a multi-level architecture ( McCrea and Rybak, 2008 ; McLean and Dougherty, 2015 ; Ausborn et al, 2021 ; Grillner and Kozlov, 2021 ; Klishko et al, 2021 ). In the former, unit-bursts generators do not receive common flexor- and extensor-related rhythmic inputs and can be flexibly reorganized by sensory and/or central inputs to meet mechanical demands of various motor behaviors ( Grillner, 1981 ; Carter and Smith, 1986 ; Grillner and Kozlov, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Eighth Edition” ( National Research Council of the National Academies, 2011 ) and were approved by the Institutional Animal Care and Use Committee of the Georgia Institute of Technology (protocol number A13063). Five adult female cats (mass 3.27 ± 0.55 kg, Table 1 ) participated in this and our previous studies and underwent previously described surgical and experimental procedures ( Maas et al, 2010 ; Hodson-Tole et al, 2012 ; Mehta and Prilutsky, 2014 ; Gregor et al, 2018 ; Klishko et al, 2021 ). Briefly, the animals were trained to walk on a plexiglass enclosed walkway using food rewards.…”
Section: Methodsmentioning
confidence: 99%
“…However, these effects appear to be limited to two muscle groups responsible for the atypical muscle synergy during paw-shaking-the vasti (VA) and tibialis anterior (TA) muscles [37]. The phase of the VA activity burst in the cycle of real and fictive locomotion [25,[43][44][45] or real and fictive paw-shaking [19,37,38] is different from activity burst phases of other pure hindlimb extensors. This suggests a unique organization of spinal networks controlling VA motoneurons.…”
Section: Possible Organization Of a Mammalian Multifunctional Locomotor Cpg Capable Of Producing Faster Transient Rhythmic Behaviorsmentioning
confidence: 99%